Kapitalinvestitionen Südoldenburger Agrarunternehmen in den USA und deren Rückwirkungen auf die sozioökonomische Struktur ihrer Standräume - Windhorst, Hans-Wilhelm (ERDKUNDE, 1987)
Whereas we are well informed about the amount, the aims as well as the location of German capital investments in the U.S. industrial sector, the level of information on investments in agriculture has been very low until now. The paper reports about a research project funded by the German Research Foundation. The most important results can be summarized as follows: Between 1977 and 1984 the overall capital investments of German agrobusiness firms in the U.S. amounted to 350 mio. DM, 280 mio. DM alone were invested by firms from South Oldenburg, the center of intense animal production in Germany. The agrobusiness firms from South Oldenburg set up a hog farm in Indiana and two egg farms, one in Ohio another one in Pennsylvania. In addition to the creation of new jobs (575 in total) the purchase of feedstuff, fuel, building material etc.had far reaching consequences for the counties, where the farms were built. When the farms were first established, they met with strong opposition in all locations, especially from local farmers. The opposition weakened when it became obvious that they also had positive effects on the social and economic structure of the counties. The choice of locations was influenced by a number of criteria, the most important were:balance of supply for the end product, price for land and feedstuff, legal regulations regarding foreign landownership and application of manure, credit facilities of local and regional banks, scientific cooperation with university departments and the extension service of the United States Dept. of Agriculture. The most important push-factors for the German firms to invest in the U.S. were: lack of possibilities to invest in South Oldenburg, agricultural policy in the EEC and Germany, environmental problems, the lack of interest of local and regional policy in supporting agrobusiness firms, reports in mass media regarding environmental problems. The most important pull-factors were: the economic and political situation in the U.S., the dollar exchange-rate, the low price for land in the 1970s, few requirements to be met regarding environmental protection. It is almost impossible to decide if some of the capital gains will be retransferred to Germany. At the moment it looks more like further investments in the U.S.